Epigenetic Mechanisms in Psychiatric Diseases and Epigenetic Therapy - KARSLI, SEHER (WILEY-BLACKWELL, 2016)
Epigenetic mechanisms refer covalent modification of DNA and histone proteins that control transcriptional regulation of gene expression. Epigenetic regulation is involved in the development of the nervous system and plays an important role in the pathophysiology of psychiatric disorders, including depression, bipolar disorder, and schizophrenia. Epigenetic drugs, including histone deacetylation and DNA methylation inhibitors have received increased attention for the management of psychiatric diseases. The purpose of this review is to discuss the potential of epigenetic drugs to treat these disorders and to clarify the mechanisms by which they regulate the dysfunctional genes in the brain. Drug Dev Res 77 : 407-413, 2016. (c) 2016 Wiley Periodicals, Inc.
Keywords: psychiatric diseases; epigenetics; HDAC inhibitors; DNMT inhibitors; HISTONE DEACETYLASE INHIBITORS; DEPRESSIVE-LIKE BEHAVIOR; DNA METHYLATION; BIPOLAR DISORDER; GABAERGIC INTERNEURONS; SYNAPTIC PLASTICITY; NEUROTROPHIC FACTOR; LYSINE METHYLATION; PREFRONTAL CORTEX; MAJOR DEPRESSION